A Phenomenological Inquiry on National Learning Camp Implementation: Basis for Program Recalibration - Dichoso, David (International Journal of Arts, Sciences and Education, 2025)
The implementation of the National Learning Camp as a recovery program of DepEd, confronted the stakeholders with challenges in its initial years. This transcendental phenomenological inquiry investigated the lived experiences of stakeholders: Learning Camp Volunteers (LCVs), learners who attended English classes, and school administrators along Context, Input, and Process evaluation. In this formative evaluation, the participants were selected using criterion-purposive sampling, and the researcher developed a semi-structured questionnaire with a scale content validity index (S-CVI) average of 1.00. Optimizing Colaizzi’s Method of Analysis, the themes in the context evaluation are stakeholders’ motivation, foregoing challenges: English language learning difficulties, teachers’ work and life balance, and logistics concerns. Input evaluation uncovered teachers’ insights on the NLC resources, and students’ experiences from the three subcamps: Intervention, Consolidation, and Enhancement. The Process evaluation unveiled the NLC structure and teaching strategies, advantages of collaboration, reflection of the stakeholders’ experiences, and implementation challenges encountered. Based on the findings, the study recommends policy recalibration to mandate students who need remediation to participate in the NLC, increase teachers’ incentives, improve learning resources and its earlier reproduction, and enhance strategies to ensure learners’ participation. These recommendations aim to recalibrate the NLC implementation, investing to learner’s English language literacy.